The abduction of children by strangers and nonfamily members: estimating the incidence using multiple methods - Finkelhor, David (Journal of interpersonal violence, 1992)
This study used three approaches to estimate the incidence of nonfamily abductions of children for 1988: a national survey of households with children, a national survey of police records, and an analysis of FBI homicide data. Estimates were derived for three differently defined types of events: stereotypical kidnappings, in which a stranger perpetrator took a child overnight, or a distance of 50 miles or more, or killed, ransomed, or evidenced an intent to keep the child permanently 200 to 300 children; legal-definition nonfamily abductions, in which a stranger or other nonfamily member took, detained, or lured a child, often in conjunction with another crime such as sexual assault 3,200 to 4,600 children; and attempted abduction, in which an unsuccessful attempt was made to take, detain, or lure a child 114,600 children